2015
DOI: 10.3390/nu7075156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weight Loss on Plasma Leptin and Adiponectin in Overweight-to-Obese Post Menopausal Breast Cancer Survivors

Abstract: Women who are obese at the time of breast cancer diagnosis have higher overall mortality than normal weight women and some evidence implicates adiponectin and leptin as contributing to prognostic disadvantage. While intentional weight loss is thought to improve prognosis, its impact on these adipokines is unclear. This study compared the pattern of change in plasma leptin and adiponectin in overweight-to-obese post-menopausal breast cancer survivors during weight loss. Given the controversies about what dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 74 publications
(110 reference statements)
6
13
2
1
Order By: Relevance
“…Several studies that offered lifestyle interventions to BC survivors have reported significant decreases in leptin (Befort et al, 2012;Rogers et al, 2013;Scott et al, 2013;Thompson et al, 2015). In our study, leptin concentrations decreased by 13% but this decrease did not reach statistical significance.…”
Section: Change In Body Mass Index (Kg/m 2 )contrasting
confidence: 81%
See 2 more Smart Citations
“…Several studies that offered lifestyle interventions to BC survivors have reported significant decreases in leptin (Befort et al, 2012;Rogers et al, 2013;Scott et al, 2013;Thompson et al, 2015). In our study, leptin concentrations decreased by 13% but this decrease did not reach statistical significance.…”
Section: Change In Body Mass Index (Kg/m 2 )contrasting
confidence: 81%
“…The authors indicated that part of the differences observed across studies might be due to hormonal treatment as Tamoxifen has been shown to reduce IGF1 and exercise may not be able to further reduce it. In our study, the analysis performed in participants who were not taking Tamoxifen (n = 15) showed a significant 11% decrease in (Befort et al, 2012;Rogers et al, 2013;Scott et al, 2013;Thompson et al, 2015). In our study, leptin concentrations decreased by 13% but this decrease did not reach statistical significance.…”
Section: Difference Mean (Sd) Percent Change P-value Bcontrasting
confidence: 71%
See 1 more Smart Citation
“…Protani et al carried out between 1963-2005, meta-analysis of 43 examinations among women diagnosed with cancer. The group of women who were already obese when the disease was recognized was characterized by a 33% higher mortality risk than women with normal body weight [22,23]. Hauner et al came to similar conclusions by assessing examinations and metaanalyses which were published between 1996-2010 [24].…”
Section: Diet In 2007 World Cancer Research Fund / Americanmentioning
confidence: 88%
“…Unlike leptin, circulating concentrations of adiponectin, increase during weight/adipose tissue loss (Ma et al, 2016;Thompson et al, 2015). Adiponectin can reduce androgen secretion.…”
Section: Nutrient Restriction and Variations In Androgen Productionmentioning
confidence: 99%